The most disreputable trade : publishing the classics of English poetry, 1765-1810 - Bonnell, Thomas Frank, 1953- (Oxford University Press, 2008)
This title probes the origins of mass-market series of literary 'classics'. Highly informative about the book trade in the late 18th and early 19th centuries, Bonnell's study is also rich in details about book illustration, copyright law, canon formation, consumer culture, and the history of reading.